Tourists' perceptions of responsibility: an application of norm-activation theory. Issue 2 (1st February 2017) - Gao, Jun; Huang, Zhuowei (Joy); Zhang, Chaozhi
ABSTRACT: Drawing on norm-activation theory, this study explores the link between tourists' perceptions of the negative impacts of tourism and their perceived responsibility. A proposed theoretical framework was examined and verified through exploratory and confirmatory research processes. Self-administered questionnaires were collected at two UNESCO World Natural Heritage Sites in China. The findings of this research suggest that tourists' perceptions of the negative impacts of tourism positively affect their ascription of responsibility, which positively influences tourists' perceptions of responsibility. Nevertheless, the accessibility of information about tourism impacts is far from enough to foster in tourists a sense of responsibility, which is important for the promotion of responsible behaviours. Several practical implications are provided to address tourists' sense of responsibility, including enhancing tourists' awareness of negative tourism impacts, increasing the availability and accessibility of information about tourism impacts, and recommending behaviours for tourists to make a positive difference to destinations.